Design, Synthesis and Study of Non-Linear Optical Properties of Phenyl Bridged Diphenylamine-s-triazine Based Donor-Acceptor Triads Containing Different π-Acceptor Groups - Suma, C.S.; Dhanya, N.P.; Seena, S. (Asian Journal of Chemistry, 2021)
Novel donor-acceptor triads of starburst D-A-A type incorporating electron deficient triazine moiety as a non-conjugating π-spacer/acceptor with two acceptor/anchoring arms comprising of cyanoacetic acid (DTP-CYA), rhodanine-3-acetic acid (DTP-RHA), barbituric acid (DTP-BA) or thiobarbituric acid (DTP-TBA) linked to triazine core via a phenyl bridge have been synthesized. Diphenylamine is used as the donor moiety and the role of the π-spacer on the absorption spectra and other electronic properties were studied. All the compounds were tested for their non-linear optical properties and determined the non-linear absorption coefficient (β) and non-linear refractive index (n2) in DMF solutions. Improved non-linear optical properties were obtained when compared to the compounds with triazine moiety as a non-conjugating π-spacer/acceptor with rhodanine-3-acetic acid (DTOP-RHA), barbituric acid (DTOP-BA) or thiobarbituric acid (DTOP-TBA) as anchoring/acceptor groups. DTOP series compounds are in the geometry of the molecule where the phenyl π-bridge and the triazine unit are coplanar with the arylidne acceptor unit. The enhanced performance may be due to the structural variants, which expected to improve through bond coupling between the donor and the terminal acceptor parts of the molecules and all compounds show asymmetry in the electron density due to the basic donor-acceptor nature of the structure.